Adult Safeguarding Policy and Law: A Thematic Chronology Relevant to Care Homes and Hospitals. Issue 2 (8th April 2014) - Manthorpe, Jill; Stevens, Martin
Abstract : Elder abuse is a 'social problem', as illustrated by the production of policy documents and legislation that define and revise the scope and nature of the problem. This article synthesises and discusses the policy documents and legal changes that have taken place in England since 2000, when the first policy guidance to address adult safeguarding as a whole was produced. The focus of this article is on particular locations, namely care home and hospital settings, and the applicable policy and legislation. The policy documents and legal changes identified are analysed using Blumer's five phases of policy implementation and Matland's ambiguity-conflict matrix to explore their implications for policy implementation and coherence. The analysis suggests that responses to elder abuse have created different kinds of ambiguity and conflict, requiring both top-down and bottom-up policy interventions.